Starlike Functions Associated With Tanh-z and Bernardi Integral Operator - Rai, Pratima; ÇETİNKAYA, ASENA; Kumar, Sushi (Amer Inst. Mathematical Sciences-AIMS, 2022)
We determine the necessary and sufficient convolution conditions for the starlike functions on the open unit disk and related to some geometric aspects of the function tanh z. We also determine sharp bounds on second and third order Hermitian-Toeplitz determinants for such functions. Further, we compute estimates on some initial coefficients and the Hankel determinants of third and fourth order. In addition, using the concept of Briot-Bouquet type differential subordination, we establish a subordination inclusion involving Bernardi integral operator.
Keywords: Starlike Functions; Hyperbolic Tangent Function; Convolution Conditions; Hermitian–toeplitz and Hankel Determinants; Subordination Inclusions; Bernardi Integral Operator